How Sustainability Reporting Strengthens the Profitability – Firm Value Link in Coal Mining Companies - Christina Juliana; Venantius Valentino Sembiring (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This study investigates whether sustainability reporting can moderate the effect of profitability on firm value. Using a quantitative approach, it examines profitability as the independent variable, firm value as the dependent variable, and sustainability reporting as the moderating variable. The research analyses time series and cross-sectional data for 12 coal mining companies listed on the Indonesia Stock Exchange between 2020 and 2022. The findings reveal that profitability negatively impacts firm value. However, sustainability reporting moderates this relationship, enhancing firm value. This study builds on previous research by demonstrating the importance of sustainability reporting as a non-financial tool in boosting firm value. Focusing on coal mining companies with published financial and sustainability reports during 2020 to 2022, the analysis targets the specific impact of sustainability reporting within this industry.